The Effectivenes of Group Guidance with Problem Solving Technique to Improve Self-Efficacy and Task Value - Muzamil, Ahmad; Wibowo, Mungin Eddy; Purwanto, Edy (Jurnal Bimbingan Konseling, 2019)
This research aimed to determine the effectiveness of group guidance services with problem solving technique to improve the self-efficacy and task value of the students of Demak Al Ma'ruf Integrated Islamic Junior High School (SMP Islam Terpadu Al Ma’ruf Demak). In order to pursue such objective, the research used pre-test post-test control group research design. Meanwhile, to collect the data, the researchers used self-efficacy and task value scales. Those scales were given to the subjects in this research amounted to 20 students divided into experimental group totaling 10 students and control group of 10 students. Further, MANOVA results showed that there were some effects of group guidance with problem solving technique on the improvement of self-efficacy (F(1.18) = 334.176, p > 0.01) and task value (F(1.18) = 309.121, p > 0.01). Therefore, this research proves that the implementation of group guidance with problem solving technique is effective to improve the self-efficacy and task value of the students of SMP Islam Terpadu Al Ma’ruf Demak.